2017
DOI: 10.3390/laws6040033
|View full text |Cite
|
Sign up to set email alerts
|

The Inclusion of the Lived Experience of Disability in Policymaking

Abstract: This paper examines the process under way in Iceland to align national law with the UN Convention on the Rights of Persons with Disabilities, focusing on the Convention's call for the active involvement of disabled people and their representative organizations in policy and decision making on matters that affect them. The paper draws on comments submitted by Icelandic DPOs on draft legislation intended to replace the existing law on services for disabled people, focusing on comments relating to their ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…This paper focuses on the strategies and emphasis adopted by the key DPOs that joined forces and formed a joint working group, which also included representation from the research community, to present a united front in the final stretch of consultations with the Icelandic authorities on the new draft disability legislation. An examination of the DPOs' strategies at this stage of the process was considered pertinent as a study of earlier stages of the process had revealed a lack of political interest on the part of the authorities, including in changing established process norms to ensure the full and effective participation of DPOs in law and policy making, as called for by Article 4.3 of the CRPD (Löve et al 2017;Löve et al 2018).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This paper focuses on the strategies and emphasis adopted by the key DPOs that joined forces and formed a joint working group, which also included representation from the research community, to present a united front in the final stretch of consultations with the Icelandic authorities on the new draft disability legislation. An examination of the DPOs' strategies at this stage of the process was considered pertinent as a study of earlier stages of the process had revealed a lack of political interest on the part of the authorities, including in changing established process norms to ensure the full and effective participation of DPOs in law and policy making, as called for by Article 4.3 of the CRPD (Löve et al 2017;Löve et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…They represent a radical change to established norms and processes, where disabled people, through their representative organizations, are recognized as capable and entitled participants who can demand and expect their contributions to be both welcomed and facilitated through reasonable accommodations and support. The call for full and effective participation of disabled people "brings them into the democratic process as contributing participants in the development of solutions to policy issues that take into account different perspectives and needs, in addition to their own" (Löve et al 2017).…”
Section: The Right To Full and Effective Participationmentioning
confidence: 99%
See 3 more Smart Citations